PENGARUH BLENDED MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN PEMAHAMAN KONSEP SISWA PADA MATERI DAUR AIR - Roni Hamdani, Acep (STKIP Subang, 2015)
This research is motivated by not maximal enhancement of the ability of learning outcomes concept understanding and solving problems in material recycling water using problem based learning model. Through this research studied solutions to solve these problems, by performing learning using a blended model of Problem Based Learning. The shape Blended conducted among which are: the provision of stimulus in the form of audiovisual media before and when learning, students are given assignments in connection with the matter further, so that students read many books about the matter further and ready to learn, provide encouragement and approaches for learning, and improve the effectiveness of learning time. The purpose of this study is to provide solutions to improve understanding of concepts and problem solving in science subjects in grade V. The experiment was conducted in SDN Tanjung III Subang using a quasy-experimental methods. For the experimental group performed several Blended allegedly able to complete lack of problem based learning model, while for the control class performed the usual problem based learning model. The instrument used to conduct research that is: test the ability of understanding the concept and problem solving as well as observation sheets teacher activity and student responses. The results showed differences in the ability of understanding the concept and problem solving significant between experimental class and control class, n-gain Blended problem based learning model is better than usual, and there is increased activity of teachers and students' responses to learning.